2020
DOI: 10.1177/0957650920951100
|View full text |Cite
|
Sign up to set email alerts
|

Parametric studies on interacting parameters influencing heat pipe performance

Abstract: The performance of a heat pipe is governed by many parameters, the effects of which may influence each other. Hence, it is utmost important to optimize the combination of these parameters for an effective energy transfer in a heat pipe. In the present study, the interacting effects of four different parameters affecting the effectiveness of heat pipe are studied namely the fluid filling ratio (20%, 30%, 40%), the pressure inside the heat pipe (0.2 bar, 1 bar, 1.8 bar), the number of wick layers (0, 1, 2) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…At lower pressure 0.0799 bar thermal resistance value is 0.15,353 K/W, whereas at the other evacuation pressure value is 0.368,041 K/W, 0.37,343 K/W, 0.456,344 K/W for 0.3466 bar, 0.6133 bar and 1.0132 bar receptively. Kumar et al 26 also observed better performance at lower pressure. After 40 W of heat input, the thermal resistance value is approximately the same at 0.0799 bar Figure 7(d) shows thermal resistance variation for different evacuation pressure at 90% FR.…”
Section: Resultsmentioning
confidence: 88%
“…At lower pressure 0.0799 bar thermal resistance value is 0.15,353 K/W, whereas at the other evacuation pressure value is 0.368,041 K/W, 0.37,343 K/W, 0.456,344 K/W for 0.3466 bar, 0.6133 bar and 1.0132 bar receptively. Kumar et al 26 also observed better performance at lower pressure. After 40 W of heat input, the thermal resistance value is approximately the same at 0.0799 bar Figure 7(d) shows thermal resistance variation for different evacuation pressure at 90% FR.…”
Section: Resultsmentioning
confidence: 88%